The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/14767058.2021.1962843
|View full text |Cite
|
Sign up to set email alerts
|

Maternal periconceptional nutrition matters. A scoping review of the current literature

Abstract: Background: The importance of nutrition in reproductive health is widely acknowledged with special emphasis given to periconceptional maternal diet and its implications on embryo-fetal development, pregnancy complications, and the health of the offspring. Methods: Following the PRISMA guidelines, we searched for literature in PubMed, CINAHL, and WoS to gather newer information on how diet composition influences the concepts from the very early stages of pregnancy and how maternal health may be affected as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
(89 reference statements)
0
8
0
Order By: Relevance
“…Maternal nutrition at conception affects placental development and function, as well as fetal genomic imprinting/programming and, consequently, the child's long-term health. 16,17 However, a thorough review of the dietary intakes of nutrients in adolescent girls and women of reproductive age in low-and middleincome countries reported that dietary deficiencies such as low iron, vitamin A, iodine, and zinc and/or calcium, remain prevalent despite the reduction in underweight mothers. 18 In high-income countries, a typical diet that includes a high intake of red meat, refined grains/ sugars, and high-fat dairy products is also lacking in several important micronutrients, such as magnesium, iodine, calcium, and vitamin D. 19 To address these issues, FIGO developed a simple Nutrition Checklist that includes questions on specific dietary requirements, body mass index (BMI), diet quality, and micronutrients.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal nutrition at conception affects placental development and function, as well as fetal genomic imprinting/programming and, consequently, the child's long-term health. 16,17 However, a thorough review of the dietary intakes of nutrients in adolescent girls and women of reproductive age in low-and middleincome countries reported that dietary deficiencies such as low iron, vitamin A, iodine, and zinc and/or calcium, remain prevalent despite the reduction in underweight mothers. 18 In high-income countries, a typical diet that includes a high intake of red meat, refined grains/ sugars, and high-fat dairy products is also lacking in several important micronutrients, such as magnesium, iodine, calcium, and vitamin D. 19 To address these issues, FIGO developed a simple Nutrition Checklist that includes questions on specific dietary requirements, body mass index (BMI), diet quality, and micronutrients.…”
Section: Nutritionmentioning
confidence: 99%
“…Maternal nutrition at conception affects placental development and function, as well as fetal genomic imprinting/programming and, consequently, the child's long‐term health 16,17 …”
Section: Preconception Checklist: Key Factors To Be Addressedmentioning
confidence: 99%
“…During the entire reproductive period-but especially in pregnancy-both environmental exposures and lifestyles can affect physiological and pathological conditions in mothers and in future generations [14][15][16]. Maternal diet-which is one of the main determinants of adverse outcomes defined above-plays a key role in ensuring the correct development and growth of newborns [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…During the entire reproductive period-but especially in pregnancy-both environmental exposures and lifestyles can affect physiological and pathological conditions in mothers and in future generations [14][15][16]. Maternal diet-which is one of the main determinants of adverse outcomes defined above-plays a key role in ensuring the correct development and growth of newborns [16][17][18][19][20][21][22]. Although many studies evaluated the relationship of single nutrients and foods with pregnancy and neonatal outcomes [23][24][25][26][27][28][29][30][31][32][33][34][35][36], these elements are not consumed alone but in complex dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition during the periconceptional period and pregnancy emerges as a critical determinant for fetal development, growth, and overall wellbeing. Inadequate nutrition can disrupt the normal development and growth of organs, including the hypothalamic-pituitary-gonadal axis (HPA-axis), thereby potentially affecting endocrine, reproductive health, and fertility in adulthood ( 7 ).…”
mentioning
confidence: 99%